An Evaluation of Attractants to Increase Catch Rates and Deplete Age‐0 Common Carp in Shallow South Dakota Lakes. (16th May 2016) - Carl, Dray D.; Weber, Michael J.; Brown, Michael L.
Abstract: Common Carp Cyprinus carpio is a highly invasive species that can alter shallow aquatic ecosystems from clear to turbid water. Although mechanical removals are commonly used to control abundance of adult Common Carp, harvest models suggest that removing age‐0 Common Carp also reduces recruitment. Attractants often improve fisheries sampling and commercial harvest and may provide a tool to increase catch rates of age‐0 Common Carp. However, techniques and attractants that target age‐0 Common Carp have not been evaluated. Our objective was to compare catch rates and size distribution of age‐0 Common Carp captured in cloverleaf traps with and without bait (fish meal or bloodworms) or light attractants. To assess whether trapping decreased the abundance of age‐0 Common Carp, we also evaluated (1) the total number and proportion of age‐0 Common Carp removed from the populations and (2) whether catch rates declined temporally as a result. Traps were fished in emergent vegetation for 5–6 nights in two shallow lakes in South Dakota during August 2010. Catch rates of age‐0 Common Carp did not differ among attractants and the control. However, catch rates declined through time, and 3, 102 age‐0 Common Carp were removed from the two lakes. Depletion population estimates indicated at least 83% of age‐0 Common Carp from Brant Lake and 21% (lower limits, 95% confidence intervals) of age‐0 Common Carp from Whitewood Lake were removed, suggesting trapping may be successful at depleting abundance. Lighted traps caught larger age‐0 Common Carp than did control traps or traps baited with bloodworms or fish meal. These results suggest that the attractants evaluated here do not increase catch rates of age‐0 Common Carp. Nonetheless, cloverleaf traps may reduce abundance of age‐0 Common Carp and have value in integrated management plans for this species. Received August 6, 2015; accepted January 6, 2016 Published online May 16, 2016